MODEL OF INTEGRATION OF FORMAL AND INFORMAL EDUCATION FOR STUDENT-ATHLETES - Almaz Galimov; Liubov Botova; Andrey Nazarenko; Marat Galyautdinov (Scientific Publishing House. NSA Press, 2019)
A majority of the students at physical education universities are actual athletes who have "double career". They combine getting professional education with professional sport activities. In this regard, sport activities of students form an important part of their future career, because it is the informal way of getting professional knowledge and skills. However, today there are no officially recognized organizational and pedagogical approaches to the formalization and assessment of informal education outcomes, which student-athletes demonstrate during their sport activities. Consequently, there are very few practices of making individual university programs for student-athletes based on their informal education outcomes. The study purpose was to develop and approbate a model of substantial integration of study process and sport training at the sports university as a method of combination of formal and informal education types for student-athletes. The study included a comparative analysis of educational and professional standards, elaboration of measures for substantial integration of sport and educational process, and study of athletes' academic performance. In addition, we used methods of modeling, interviewing, expert assessment and mathematical statistics in our study. The study revealed the coherence of athletes' knowledge, skills and activities and the competencies they acquire at the sports university. We demonstrated that elite athletes gain knowledge, skills and attitudes envisaged in the educational program in the framework of their sport activities. We have designed the model of individual university program for elite athletes, which corresponds to the techniques of integration of formal and informal education types.